Implementation of the Project-Based Learning Model in Learning Short Story Review Writing Skills - Miftahir Riska; Nursaid; Afnita; Dewi Syafrina (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe: 1) the results of the pre-test of short story review writing skills; 2) the procedure for implementing the Project-Based Learning (PjBL) model in learning short story review writing skills; 3) the results of the post-test of short story review writing skills in learning using the PjBL model using LKPD; 4) the effect of using the PjBL model in learning short story review writing. This study uses a descriptive method that took place in the odd semester of the 2025/2026 academic year at SMK Negeri 3 Pandang. The subjects of the study were grade XI students who participated in the pre-test of short story review writing activities, learning to write short story reviews using the PjBL model through LKPD, and participated in the post-test of short story review writing skills in learning using the PjBL model using LKPD. They numbered 34 students. Short story review writing skills were collected using a performance test instrument. Learning procedure data were collected using non-test instruments, namely teacher and student observation guidelines and questionnaires. The learning procedure data were analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusions. The pre-test and post-test data were collected using a performance test instrument. The results of the study showed: 1) the pre-test results of writing short story reviews were in the moderate category; 2) the learning procedure for writing short story reviews involved initial activities, core activities, and final activities; 3) the post-test results of writing short story reviews in learning using the PjBL model were in the high category; showing an increase in learning outcomes for writing short story reviews for each indicator; 4) the application of the PjBL model was proven to have a positive effect because it was able to improve short story review writing skills.